STRATEGI INDONESIA MEMBENTUK CYBER SECURITY DALAM MENGHADAPI ANCAMAN CYBER CRIME MELALUI BADAN SIBER DAN SANDI NEGARA - Yusep Ginanjar (Dinamika Global : Jurnal Ilmu Hubungan Internasional, 2022)
Cyber security has become a priority issue for all countries in the world since information and communication technology is used in various aspects of life, both in social, economic, legal, organizational, health, education, culture, government, security, defense, and other aspects. In direct proportion to the high level of utilization of information and communication technology, the level of risk and threat of misuse of information and communication technology is also getting higher and more complex. In response to these events, Indonesia then formed the National Cyber and Crypto Agency (BSSN) as a model for national cyber security institutions. This study uses a qualitative method with a descriptive approach. The purpose of this research is to find out how Indonesia's strategy in establishing cyber security in dealing with the threat of cyber crime through the National Cyber and Crypto Agency.